Report of the Steering Committee on Empowerment of Women and Development of Children for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Report of the Steering Committee on ‘Empowerment of Women and Development of Children’ for the Tenth Five-Year Plan (2002–2007), prepared by the Planning Commission, presents a comprehensive review of policies, programmes, institutional mechanisms, and legislative frameworks concerning women and children in India, with the objective of strengthening strategies for inclusive development during the Plan period. Chaired by Dr. K. Venkatasubramanian, the Committee was tasked with evaluating the progress of the Ninth Plan, assessing the implementation of the Women’s Component Plan, examining the effects of economic reforms and globalization on vulnerable groups, and recommending corrective measures to enhance the flow of benefits to women and children across sectors. The report systematically analyzes demographic trends, literacy, health indicators, workforce participation, political representation, child mortality, malnutrition, enrolment ratios, and financial allocations, highlighting both achievements and persistent challenges such as gender disparities, violence against women, high maternal and infant mortality, malnutrition, and school dropout rates. It underscores the need for improved enforcement of women- and child-specific legislation, strengthened institutional arrangements at central and state levels, greater devolution of powers to Panchayati Raj Institutions under the 73rd and 74th Constitutional Amendments, and enhanced collaboration with NGOs. Additionally, recognizing adolescents as a neglected demographic, the report incorporates focused recommendations for their welfare and development. Emphasizing targeted physical and financial goals, the Committee proposes an integrated, gender-sensitive, and child-centric planning approach to accelerate empowerment, ensure equitable resource allocation, and promote sustainable human development outcomes during the Tenth Plan period.
Government of India Planning Commission October - 2001
Keywords: Empowerment Of Women; Development Of Children; Tenth Five-Year Plan; Women’s Component Plan; Gender Equality; Child Welfare; Institutional Mechanisms; Panchayati Raj Institutions; Economic Liberalization Impact; Legislative Review; Adolescent Development; Financial Outlays